Análise dos testes alérgicos cutâneos de leitura imediata e IgE's específicas a reatividade do TPO com assados de leite e ovo - Vilar, Lisis Karine (2018)
Introduction: The most common food allergies (FA) in childhood are cow's milk (CM) and hen’s egg (HE), affecting 1.4- 3.8% and 1- 2.6%, respectively in the USA, Europe and Brazil. Approximately 60 to 80% of FA patients tolerate baking products with the allergen, making their introduction an alternative to the traditional treatment of total allergen exclusion, reducing nutritional risk and negative impact on the quality of life of the child and their relatives. Data on the correlation of allergic tests and tolerance or intolerance to milk and egg in baked goods are still limited. Objective: Describe the correlation of skin allergic puncture tests and specific IgEs (Immunocap) to the reactivity of OFC performed with baked in patients with cow's and egg allergy in a Brazilian sample. METHODS: A cross-sectional study was carried out with a convenience sample, in which patients who were eligible for OFC performed the skin prick test (SPT) with the allergen in natura, baked (cake -30min / 180 ° C), boiled and with extracts after we offered ¼ of the cake, every 20 min. until the total consumption (1.3 g of cow's milk protein / portion or 2.2 g of egg protein / portion). We consider tolerant those who did not present objective clinical manifestations. Patients who presented tolerance were later submitted to OFC with the allergen in nature. Results: We performed 54 oral provocations with baked milk and 42 with baked egg, where 72% (39) and 66% (14) presented tolerance to the baked protein in the form of cake, respectively. The median age was 1 year and 1 month (6 m -15 years) for those taking the OFC with Baked milk and 3 years and 9 months (6 m-11 years) for the baked egg group. Although it is an alternative to traditional treatment, the risk of serious reactions exists, in our cohort 2 patients required epinephrine during OFC with baked milk. The analysis of the allergic tests between the reactive and tolerant groups for both allergens (CM and HE) presented statistical difference only for CM IgE (13.2 κU/L and 3.2 κU/L) with p = 0.028 and for casein SPT (5.5 mm and 2.5 mm) p = 0.027, respectively. IgE for CM and SPT for casein had the best predictive negative (NPV) of 80% to predict OFC with baked. While SPT with egg white presented better performance (100% NPV) when compared to IgE and SPT for ovomucoid (OM) with 85% NPV, to predict OFC with processed egg. Conclusion: Our work reinforces data from the international literature, being the first to describe the correlation of allergic tests with OFC outcomes, in a sample of the Brazilian population. Providing clinical indicators with easy access and low cost in the management of patients with FA and tools to avoid unnecessary repetition of OFC.